Mewujudkan Kesejahteraan Sosial melalui Diseminasi Hasil Pengabdian di Desa Dlanggu, Lamongan - Rozi, Ahmad Fathur; Riza, Cahyani Syahrur; Azizah, Nur; Sundari, Ariefah; Nasikhin, Muh. Nur Ali Khoirun (Jurnal Pemberdayaan Umat, 2025)
Purpose: This community service initiative aims to enhance social welfare in Dlanggu Village, Deket District, Lamongan Regency by disseminating community service outcomes. The program focused on empowering local communities through poverty alleviation, education improvement, and sustainable livelihood development. Methodology: This study employed participatory rural appraisal (PRA), surveys, and focus group discussions (FGDs) to identify community needs and priorities. Data were analyzed using Microsoft Excel and SPSS to evaluate the program's impact on community awareness, skills, and access to resources, particularly in agriculture, entrepreneurship, and education. Results/Findings: The results revealed significant improvements in community awareness, skills, and access to resources. The key outcomes included increased participation (78%), enhanced income levels (65%), and stronger social cohesion (72%). However, challenges, such as limited infrastructure and human resources, were identified, which affected the program's scalability. Conclusions: The program successfully enhanced social and economic welfare through participatory approaches, skill training, and economic empowerment. This demonstrates the effectiveness of community engagement in driving sustainable development. Limitations: The study was constrained by its short-term implementation, reliance on self-reported data, and small sample size, which may limit the generalizability of the findings. Contributions: This initiative offers a replicable model for rural development, providing valuable insights for policymakers, NGOs, and researchers focusing on social welfare and sustainable development.